Glenna and her Photographer - Pickford, Joel:::::::::
Glenna Pipes Pickford, left, and her best friend and wedding photographer, Rue Farris 'Moophie' Drew. Drew went on to became a photographer for Look magazine and, later, a New York publicist. This photograph was taken by her husband, Robert Drew, who would later pioneer the documentary film genre known as Cinema Verité. At the time of the wedding, Drew was serving in the U.S. Air Force at Lemoore Naval Air Base. Starting his post military career in the 1950s as a Life magazine writer and editor, Drew went on to become a TV producer at CBS. There he made groundbreaking documentary films such as Primary (1960) and Crisis: Behind A Presidential Commitment (1963) that eschewed interviews and voice over narration in favor of unscripted footage and dialog. His production company Drew Associates launched the careers of such luminaries of filmmaking as D.A. Pennebaker, Albert and David Maysles, Richard Leacock, and Ridley Scott. French film theorists later coined the term cinema verité to describe the new genre of unscripted filmmaking.